Laser-induced acoustic waves for measurement and imaging - Li, W; Roy, R; Cleveland, R; Berg, L; DiMarzio, C (2000)
A short pulse of laser light can act as a source of acoustic energy for acoustic imaging. Although there are a number of mechanisms by which the light pulse may generate sound, all require a pulse of high peak power density and short duration. In this work, we address examples where the material is highly absorbing at the laser wavelength, and the sound is generated near the surface. In these cases, there exist two different mechanisms which can convert the light to sound. The first is heating followed by expansion, and the second is generation of a plasma in the air above the surface. In the first case, sound generation occurs in the medium of interest and the energy efficiency can be very high, in the sense that no reflection losses occur. We present two applications from our own research.